Notas sobre Vismia guianensis (Aubl.) Choisy e suas novas variedades. - Berg, Maria Elisabeth van den (Museu Paraense Emilio Goeldi, 2011)
Vismia guianensis (Aubl.) Choisy, a very common species in Trop. America, has remarkable variations that the author tries to explain founded on ecological data, concerned to the ocurrence of that species in the Aamzonian Region. Synonymy and some lacks in this original discription, and pollen morphology as well as the geographical distribution and the dispersion by chiroptera are discussed here. Six new varieties are described and, jointily with others, ilustred.